Roll waves evolution in high gradient channels to a non-Newtonian rheology - Maciel, G. F. [UNESP] (Civil-Comp Press, 2002)
The criteria for the occurrence of roll wave phenomenon in the supercritical and turbulent Newtonian and non-Newtonian flows from the engineering point of view was analyzed. Imposing a constant discharge at the upstream of the canal and superposing a small perturbation, it was observed that roll waves can be developed more easily for small wave numbers and for high cohesions. Moreover, from the mathematical model used, it was demonstrated that the numerical viscosity was 10 times the physical viscosity.
Keywords: Bingham fluid; Roll wave; Shallow water; Computer simulation; Mathematical models; Perturbation techniques; Reynolds number; Viscosity; Waves; Godunov-VanLeer schemes; Roll waves; Rheology